2017
DOI: 10.1089/ars.2016.6800
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect of Dimethyl Fumarate in an MPTP-Mouse Model of Parkinson's Disease: Involvement of Reactive Oxygen Species/Nuclear Factor-κB/Nuclear Transcription Factor Related to NF-E2

Abstract: Aim: Oxidative stress plays a key role in Parkinson disease (PD), and nuclear transcription factor related to NF-E2 (Nrf-2) is involved in neuroprotection against PD. The aim of the present study was to investigate a role for nuclear factor-jB (NF-jB)/Nrf-2 in the neurotherapeutic action of dimethyl fumarate (DMF) in a mouse model of PD and in vitro in SHSY-5Y cells. Results: Daily oral gavage of DMF (10, 30, and 100 mg/kg) significantly reduced neuronal cell degeneration of the dopaminergic tract and behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 71 publications
1
101
0
1
Order By: Relevance
“…Newly, it was identified that insufficient Nrf2 activation in humans is linked to chronic diseases such as PD , AD and amyotrophic lateral sclerosis . Our findings provide elucidation of the molecular mechanisms involved in the neuroprotective action of DMF, evidencing the importance of the cell survival signalling pathways regulated by Nrf2 in term of oxidative stress.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Newly, it was identified that insufficient Nrf2 activation in humans is linked to chronic diseases such as PD , AD and amyotrophic lateral sclerosis . Our findings provide elucidation of the molecular mechanisms involved in the neuroprotective action of DMF, evidencing the importance of the cell survival signalling pathways regulated by Nrf2 in term of oxidative stress.…”
Section: Discussionmentioning
confidence: 57%
“…Recent experimental studies have shown that DMF exerts beneficial effects in preclinical models of neuroinflammation and neurodegeneration : in vitro, it has been shown to protect SH‐SY5Y cells against 6‐OHDA‐induced neurotoxicity and the brain from oxidative stress via Nrf‐2‐dependent mechanisms . Moreover, in an in vivo model of Parkinson, DMF significantly reduced neuronal degeneration of dopaminergic tract and behavioural impairments .…”
Section: Discussionmentioning
confidence: 99%
“…In TBI, DMF effect has been associated with increase in NRF2, manganese superoxide dismutase (MnSOD), and HO‐1 and a decrease in inflammation via modulation of immune response genes such as IL‐1 and TNF‐α . Similar neuroprotective roles of DMF were observed in epileptic rats, while in HD, AD and PD; all of which are characterized by oxidative stress and neuroinflammation, DMF can reduce the severity of oxidative stress by upregulating NRF2, MnSOD, and HO‐1 levels and by downregulating IL‐1 and cyclooxygenase 2 (COX‐2) levels …”
Section: Preclinical and Clinical Activities In Inflammatory Diseasesmentioning
confidence: 96%
“…The therapeutic benefits of DMF have been shown in other acute and chronic neurological disorders; including stroke, traumatic brain injury (TBI), epilepsy, Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease (HD), which are all associated with oxidative stress and/or inflammation. DMF can induce increased expression of antioxidative genes by activating the NRF2 cellular defense machinery against oxidative stress.…”
Section: Preclinical and Clinical Activities In Inflammatory Diseasesmentioning
confidence: 99%
“…Many studies state that oxidative stress could be the major cause of neurodegenerative disorders such as Parkinson and Alzheimer's disease (26,27). In neuronal culture, quercetin increases survival against oxidative insults and appears important for neuronal protection (28).…”
Section: Discussionmentioning
confidence: 99%